ASHRAE greenguide : the design, construction, and operation of sustainable buildings. (ASHRAE professional series., 2006)
"The ASHRAE GreenGuide was developed primarily to provide guidance to designers of HVAC & R systems in how to participate effectively on design teams charged with producing green buildings"--Provided by publisher